HEGEMONI, KEKUASAAN, DAN GERAKAN MAHASISWA ERA 1990-AN: PERSPEKTIF DAN ANALISA - Mohammad Maiwan (Jurnal Ilmiah Mimbar Demokrasi, 2016)
ABSTRACT The student movement that emerged in the 1990s was a response to the authoritarian New Order policies. Although New Order succeeded in economic development but lead to inequality. Student activists form an alliance with pro-democracy groups such as NGOs, unions, farmers, and critical opposition groups. Therefore, their movements become an important part of the pro-democracy movement. In general the issues presented students are: First, the issues of democratization and human rights. Secondly, issues related to land, environment and labor. In addition to address issues of local and national, their movements also a response of international issues To control the student movement, the government established the SMTP (Student Senate Higher Education), accompanied by harsh measures. Nevertheless, their movement is still weak and disunited. The existence of a strong student movement and spread emerge when the economic crisis hit Indonesia, dropping of President Soeharto in May 1998. Keywords: Student movement, politics, New Order, 1990s-era.